2021
DOI: 10.1155/2021/1036068
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Jiawei Danggui Beimu Kushen Pills in the Treatment of Prostate Cancer and Their Influence on the Expression of Serum Prostate Specific Antigen

Abstract: Objective. To observe the clinical effects of Jiawei Danggui Beimu Kushen pills in treating prostate cancer and their influence on the expression of serum prostate specific antigen. Methods. A total of 234 prostate cancer patients were selected and randomly divided into observation group and control group, with 117 cases in each group. The control group was given oral bicalutamide tablets, while the observation group was treated with Jiawei Danggui Beimu Kushen pills on the basis of the control group. The trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The observation group could significantly reduce the serum PSA level, inhibit tumor vitality, and improve the clinical symptoms of patients. Long-term follow-up found that the observation group could improve the five-year cumulative survival rate, the incidence of adverse reactions was lower than the control group ( Zhao et al, 2021 ). Gai et al (2021) explored the effect of combining TCM with hormonal therapy for prostate cancer patients.…”
Section: Clinical Practicementioning
confidence: 91%
“…The observation group could significantly reduce the serum PSA level, inhibit tumor vitality, and improve the clinical symptoms of patients. Long-term follow-up found that the observation group could improve the five-year cumulative survival rate, the incidence of adverse reactions was lower than the control group ( Zhao et al, 2021 ). Gai et al (2021) explored the effect of combining TCM with hormonal therapy for prostate cancer patients.…”
Section: Clinical Practicementioning
confidence: 91%